Impact of Early Versus Late Antiretroviral Treatment Initiation on Naive T Lymphocytes in HIV-1-Infected Children and Adolescents – The-ANRS-EP59-CLEAC Study - Frange, Pierre; Montange, Thomas; Le Chenadec, Jérôme; Batalie, Damien; Fert, Ingrid; Dollfus, Catherine; Faye, Albert; Blanche, Stéphane; Chacé, Anne; Fourcade, Corine; Hau, Isabelle; Levine, Martine; et al. (Frontiers in Immunology, 2021)
Background: The early initiation of antiretroviral therapy (ART) in HIV-1-infected infants reduces mortality and prevents early CD4 T-cell loss. However, the impact of early ART on the immune system has not been thoroughly investigated in children over five years of age or adolescents. Here, we describe the levels of naive CD4 and CD8 T lymphocytes (CD4/CD8TN), reflecting the quality of immune reconstitution, as a function of the timing of ART initiation (early (<6 months) versus late (≥24 months of age)). Methods: The ANRS-EP59-CLEAC study enrolled 27 children (5-12 years of age) and nine adolescents (13-17 years of age) in the early-treatment group, and 19 children (L-Ch) and 21 adolescents (L-Ado) in the late-treatment group. T lymphocytes were analyzed by flow cytometry and plasma markers were analyzed by ELISA. Linear regression analysis was performed with univariate and multivariate models. Results: In children, early ART was associated with higher CD8TN percentages (medians: 48.7% vs. 31.0%, P = 0.001), and a marginally higher CD4TN (61.2% vs. 53.1%, P = 0.33). In adolescents, early ART was associated with low CD4TN percentages and less differentiated memory CD8 T cells. CD4TN and CD8TN levels were inversely related to cellular activation and gut permeability. Conclusion: In children and adolescents with a good immunovirological status, the benefits of early ART for CD8TN were clear after long-term ART. The impact of early ART on CD4TN appears to be modest, given the robust thymus-driven CD4 reconstitution in patients with late ART initiation. The ClinicalTrials.gov identifier is NCT02674867.